The comparison Study of Synthesis p-Methoxycinnamoylhydrazide by Conventional Thermal Heating and Microwave Irradiation - Sulistyowaty, Melanny Ika; Nusandari, Ratna; Rudyanto, Marcellino; Ekowati, Juni (Berkala Ilmiah Kimia Farmasi, 2024)
Previous studies had shown that ethyl p-methoxycinnamate (EPMS) had various bioactivities, such as analgesic and anti-inflammatory through COX inhibition. Due to its unique structure, this compound was modified into a selective COX-2 inhibitor. In this research, EPMS was isolated from Kaempferia galanga L. and used as a starting material to be reacted with hydrazine hydrate to obtain 3-(4-methoxyfenil)propanehydrazide. This synthesis was carried out using conventional heating and microwave irradiation. The microwave irradiation was chosen because of its potential to reduce reaction time and increase yield. Next, the crude product was purified using column chromatography to produce a pure product, where characterization and structural analyses of the compound were carried out using the TLC test, melting point test, IR, 1H-NMR, and UV spectroscopy. The results showed that the product produced was 3-(4-methoxyphenyl)propanehydrazide with a yield of 0,76% by conventional thermal heating and 7,90% by microwave irradiation. Keywords:  EPMC, Hydrazine Hydrate, 3-(4-Metoxyphenyl)propanehydrazide, Conventional Heating, Microwave Irradiation